Simulation and Analysis of Flow Process in Pneumatic Conveyors in Syrian Ports - الحموي لطيفة; سلامة احمد; عباس محمد (Latakia University Journal -Engineering Sciences Series, 2022)
The behavior of the flow of particles of the material transported through the air flow varies according to the type of material and the parameters of the conveyor, including the productivity and the dimensions of the conveyor. In This research, the optimal state of wheat flow in the Vigan 200 pneumatic conveyor in Lattakian port was studied by comparing the flow patterns results of several parameters and shapes of the transported wheat and studying the effect of each of them on the conveyor pipes and focusing on the curved parts of the pipes. Flow and erosion have been simulated by DEM-CFD method using Ansys fluent and Rocky DEM, the effect of shape and dimension changing on the erosion of the bend part of the tube, normal and tangential forces of particle- particle, have been studied, the results showed that in case of wheat particles , both of normal and tangential forces increased in bend , and gradually decreased in the horizontal pipe and the particle flow was more stability in vertical and bend pipes but a dune flow was observed in horizontal pipe, whereas normal and tangential forces significantly decreased in case of spherical particles which flow in small groups in vertical, bend and horizontal pipes. These simulations showed the great influence of particle size, shape and initial air velocity on the behavior of wheat particles flow, the results also showed that the erosion values decreased and behavior of the flow approaches the optimum state when rectangular bend was used instead of the cylindrical one when the initial air velocity reached 17.5 m/s.